Boko Haram Conflict Map. - Barton, Abigail.; Zussman, Noah.; Zheng, Norma. (Tufts University. Tisch Library., 2018)
Students in Tufts PJS150-5 Conflict Resolution (Spring 2018, Professor Amanda Donahoe) worked in small groups write a collaborative research paper, called a 'conflict map' in which they select and analyze a current world conflict and make an argument for a course of resolution. This conflict map analyzes the Boko Haram conflict in Nigeria.